The blue economy : concept, constituents and development - National Maritime Foundation (New Delhi, India). Annual Maritime Power Conference 2017 : New Delhi, India); Sakhuja, Vijay; Narula, Kapil; National Maritime Foundation (New Delhi, India) (2017)
On economic aspect of oceans around India covered in the Annual Maritime Power Conference, moderated by National Maritime Foundation, New Delhi, India in 2017.
"National Maritime Foundation."
Includes bibliographical references and index.
Keywords: Marine resources -- Economic aspects -- 21st century -- India -- Congresses; Marine resource development -- India -- Congresses